Digi-Med plus System Using Internet of Things (IoT) (International Journal of Engineering and Computer Science, 2017)
Most of the time, due to negligence of hospital staff, excessive number of patients or inattentiveness of relatives it may happen that saline bottle is not monitored properly and it may lead to cause heart attack due to “AIR EMBOLISM”. In a hospital, number of electrical equipment’s (fan, lights) are more so energy is more. Thus, it is important to use electricity as per the requirement. Thus, In this paper we have proposed a system which include combination of sensor technology and Internet of Things (IoT).Using this system one can control switch of the electricity and monitor level of the saline bottle from distant position.